Workshop Analisis dan Interprestasi Hasil Uji Statistik Menggunakan SMART PLS 3.2.8 - Leovita, Angelia; Resti, Siska; Martadona, Ilham (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
Workshop activities are carried out as a result of advances in information technology, data processing becomes a very crucial thing, especially in the context of research and development of science. Where the need for science and knowledge is increasing in mastering the software used in data analysis of a study. This activity aims to increase participants' knowledge of the concept of Structural Equation Modeling with parameter estimation using the Partial Least Square (SEM-PLS) method, (2) Improve participants' ability to process data using the Smart-PLS data processing application, (3) Interpret the results of data processing or output from the software in order to improve the quality of research. The method used is the lecture and practice method. The number of participants who attended the workshop was 23 people consisting of academics and students. The results of the training showed an increase in participants' understanding and their ability to use SMART PLS. The conclusion of this training is that mastery of PLS-SEM is important for improving the quality of research, and this kind of training can contribute positively to research.